Loss of MAPK8IP3 Affects Endocytosis in Neurons - Snead, Amanda M.; Gowrishankar, Swetha (Frontiers in Cellular Neuroscience, 2022)
Perturbations in endo-lysosomal trafficking pathways are linked to many neurodevelopmental and neurodegenerative diseases. Of relevance to our current study, MAPK8IP3/JIP3, a brain enriched putative adaptor between lysosomes and motors has been previously implicated as a key regulator of axonal lysosome transport. Since de novo variants in MAPK8IP3 have recently been linked to a neurodevelopmental disorder with intellectual disability, there is a need to better understand the functioning of this protein in human neurons. To this end, using induced neurons (i3Neurons) derived from human iPSCs lacking MAPK8IP3, we demonstrate that loss of hMAPK8IP3 affects endocytic uptake in neurons but does not affect the proteolytic activity of lysosomes in neuronal cell bodies. Our findings indicate that MAPK8IP3 may be a regulator of bulk endocytosis in neurons and that altered endocytic uptake may play a role in MAPK8IP3-linked neurodevelopmental disorders.